Rancang Bangun Alternator Mobil Menggunakan Magnet Permanen - Andareas Pangkung; A. M. Shiddiq Yunus; Mustari Nur Mulyadi; Padidi Alfrianto Illa (Politeknik Negeri Ujung Pandang, 2021)
The electric power system is one of the sources of electricity found in the vehicle which functions as a starter and electric component of the vehicle. The battery (battery) is a source of electricity to meet the electrical system in the car, but the battery is only a place to store electric charge. Therefore, there is an alternator as a power generator to charge the battery. The alternator on a car uses artificial magnets in its rotor which still require excitation. Therefore, it encourages the author to analyze the comparison of alternators using permanent magnets and artificial magnets. The problem that arises is how to compare rotation, voltage, and output power on the alternator using permanent magnets and artificial magnets. The purpose of this study was to determine the ratio of the output power generated by the alternator using permanent magnets and artificial magnets. Research and Development Methods are research methods used to produce certain products, and test the effectiveness of these products. Based on the results of the tests carried out, it was found that at the same rotation an alternator with a permanent magnet generates a greater output power than the artificial magnet. However, at the same rotation the motor requires more input power to rotate the alternator when using permanent magnets. When the alternator output voltage is the same, the rotation of the alternator using the permanent magnet is lower.